Association of decreased sympathetic nervous activity with mortality of older adults in long‐term care. Issue 1 (23rd July 2013) - Shibasaki, Koji; Ogawa, Sumito; Yamada, Shizuru; Iijima, Katsuya; Eto, Masato; Kozaki, Koichi; Toba, Kenji; Akishita, Masahiro; Ouchi, Yasuyoshi
<x xml:space="preserve">Abstract</x> Aim To investigate the relationship between physical function, mortality and autonomic nervous activity measured by heart rate variability of elderly in long‐term care. Methods Cross‐sectional and longitudinal studies were carried out at hospitals and health service facilities for the elderly in Nagano prefecture, Japan, from July 2007 to March 2011. A total of 105 long‐term care older adults and 17 control older adults with independent physical function were included. The Functional Independence Measure (FIM) and Barthel Index were determined as indices of physical function. Twenty‐four‐hour Holter monitoring was carried out. From RR intervals in electrocardiograms, heart rate and standard deviations of all NN intervals in all 5‐min segments of the entire recording, power spectral density, low frequency, high frequency and low frequency/high frequency (LF/HF) were calculated. Results FIM score and Barthel Index were 46 ± 26 and 30 ± 31, respectively, in long‐term care elderly. FIM and Barthel index were significantly correlated with heart rate and the standard deviations of all NN intervals after adjustment for age, sex, cardiovascular risk factors and FIM. Furthermore, LF/HF was significantly decreased in long‐term care elderly compared with control elderly after adjustment for covariates. In addition, decrease in LF/HF was an independent risk factor for mortality. Conclusion Low LF/HF activity was observed in long‐term care elderly and was related to an increase of overall mortality. Geriatr Gerontol Int 2014; 14: 159–166.